"Hallo" from a desolate road: Archetypal understanding of a Korean young man's musical journey. Issue 3 (27th May 2021) - Bae, Mi Hyun
ABSTRACT: Introduction : Phantasies released in analytical music therapy (AMT) manifest significant internal and external experiences in one's life. This article delineates how phantasies that portend psychological indications for one's growth come forth in the clinical context and provide a heuristic framework to understand such key unconscious materials. Method : This article presents the theoretical relevance of archetypal analysis to AMT along with an in-vivo clinical example with a Korean young man demonstrating the use of techniques to access the unconscious. The expressed symbolic experience of the case is analyzed within the framework of the hero's journey using the archetypal appraisal of Pearson. Results : This heuristic analysis identifies two key archetypes corresponding to the presented clinical case and discusses the psychological features and psychosocial development of the case in relation to these archetypes. The clinical example supports the clinical feasibility of an archetypal analysis of the phantasies expressed in music therapy. Discussion : The implications of archetypal analysis as well as its potential to enlarge and enrich the field of AMT are discussed in terms of theory, research, education, and practice.